ETHANOL EXTRACT OF MATOA (Pometia pinnata) AS NATURAL ANTIOXIDANT TO INHIBIT OXIDATION REACTION OF CRUDE PALM OIL: EKSTRAK ETANOL DAUN MATOA (Pometia pinnata) SEBAGAI ANTIOKSIDAN ALAMI UNTUK MENGHAMBAT REAKSI OKSIDASI PADA CRUDE PALM OIL - Sriwijayanti; Hidayatullah, Ryan; Musa, Weny JA; Bialangi, Nurhayati; Situmeang, Boima; Widiyanto, Holisha; Lailatussholihah, Isna (UIN Mataram, 2024)
Indonesia is the 2nd largest country in the world in terms of palm oil production. The demand for Crude Palm Oil increases every year. For this reason, Indonesia is expected to be able to compete at the international industry level in producing palm oil, with the aim of being able to produce good quality palm oil among industries in other countries. The problem that often occurs in CPO factories is a decrease in the quality of CPO caused by an increase in Free Fatty Acid (FFA) levels and Peroxide Numbers. Antioxidants are substances that can delay or prevent the occurrence of free radical anti-oxidation reactions in the oxidation of fats or oils. Natural antioxidants are antioxidants that are obtained directly from nature. Natural antioxidants are antioxidants that are obtained directly from nature. One of them is the leaf of the matoa plant (Pometia pinnata). Based on the results of this study, the antioxidants of the ethanol extract of the matoa plant can reduce levels of FFA and peroxide numbers depending on the length of time the antioxidant mixture is given to CPO. In this study, a decrease in FFA levels and peroxide numbers was obtained from samples on day - 10 with the addition of 5000 ppm antioxidants, namely 2.71%. while the peroxide number is 0.83%.